2019
DOI: 10.1002/qj.3559
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the Hines and Warner–McIntyre–Scinocca non‐orographic gravity wave drag parametrizations

Abstract: A column model based on CIRA wind and temperature profiles is employed to assess the characteristics of the Hines Doppler‐spread and Warner–McIntyre–Scinocca (WMS) non‐orographic drag parametrizations for internal gravity waves. The “Alexander–Dunkerton” variant of the WMS scheme is also briefly considered. This study goes into more detail than previous comparisons by performing a spectral analysis of the momentum deposition and drag, and by examining the ability of each scheme to reproduce a high vertical wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The latter strongly distorts the vertical wavenumber spectra due to Doppler shifting. Majdzadeh and Klaassen [44] have thoroughly investigated the behavior of the parameterizations [42,43] and demonstrated that they never can reproduce the saturated m = −3 slope in the background shear, even if it was prescribed by the saturation criterion. This poses a question of whether the empirical threshold of the "universal" spectrum can be used in the presence of the mean wind at all.…”
Section: Spectral Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter strongly distorts the vertical wavenumber spectra due to Doppler shifting. Majdzadeh and Klaassen [44] have thoroughly investigated the behavior of the parameterizations [42,43] and demonstrated that they never can reproduce the saturated m = −3 slope in the background shear, even if it was prescribed by the saturation criterion. This poses a question of whether the empirical threshold of the "universal" spectrum can be used in the presence of the mean wind at all.…”
Section: Spectral Schemesmentioning
confidence: 99%
“…McLandress and Scinocca [48] argued that the DSP could be further tuned, such that the averaged fields simulated by a GCM using different GW schemes were close. Majdzadeh and Klaassen [44] noted that the DSP could not reproduce the saturated m = −3 slope of the vertical wavenumber spectra in the absence of mean wind shear (similar to the scheme of [39]), because the large-wavenumber harmonics were progressively obliterated. The DST is based on the assumption that waves are conservative and non-interacting in the Lagrangian frame of reference and become nonlinear when transformed to the Eulerian frame [49].…”
Section: Nonlinear Spectral Schemesmentioning
confidence: 99%
“…But this approach does not account for saturation and requires an intermittency index to account for GW time scales. The spectral approaches rely on rather-arbitrary tuning of wave spectrum and abrupt critical-level absorption of harmonics resulting in a non-physical strain on simulated flow (Hoshino et al, 2013;Majdzadeh and Klaassen, 2019;Warner and McIntyre, 1996;Zalucha et al, 2013). Recently developed 'Whole Atmosphere' models extend GCMs to planetary exobase.…”
Section: Motivationmentioning
confidence: 99%